Frontal lobe epilepsy: an eye tracking study of memory and attention - Zhang, Qiong; Sun, Weifeng; Huang, Kailing; Qin, Li; Wen, Shirui; Long, Xiaoyan; Wang, Quan; Feng, Li (Frontiers in Neuroscience, 2023)
Objective: To explore the characteristics and mechanisms of working memory impairment in patients with frontal lobe epilepsy (FLE) through a memory game paradigm combined with eye tracking technology.We included 44 patients with FLE and 50 healthy controls (HC).All participants completed a series of neuropsychological scale assessments and a short-term memory game on an automated computer-based memory evaluation platform with an eye tracker.Results: Memory scale scores of FLE patients including digit span (U=747.50, P=0.007), visual recognition (U=766.50, P=0.010) and logical memory (U=544.00, P<0.001) were significantly lower than HC. The patients with FLE took longer time to complete the short-term memory game on the four difficult levels than healthy controls